Survey on heavy metal concentrations and maturity indices of organic fertilizer in China - Zhang, Xi; Meng, Haibo; Shen, Yujun; Li, Ji; Wang, Jiarui; Zhou, Haibin; Ding, Jingtao; Wang, Jian; Song, Liqiu (International Journal of Agricultural and Biological Engineering, 2018)
A nationwide survey of organic fertilizer was carried out in China, and 263 samples were collected to be analyzed for maturity indices (moisture content (MC), pH, electrical conductivity (EC), E4/E6, and germination index (GI)) and 7 heavy metals (Cu, Zn, Cd, Pb, Cr, As and Ni). The MC, pH, EC, E4/E6 and GI showed large variations among the organic fertilizer samples with ranges of 6.9%-66.68%, 4.40-9.19, 0.76-13.38 mS/cm, 1.07-9.40, and 10%-150%, respectively. The concentrations of 7 heavy metals (Cu, Zn, Cd, Pb, As, Cr, Ni) were also with large variations at 7.53-580.4, 0-2818, 0.02-149.3, 0 (not detected)-1321, 0.14-26.9, 3.70-1237, and 0 (not detected)-214.6 mg/kg dry weight. Compared with the limit values of the Chinese standard for organic fertilizers (NY525-2012), 9.51%, 73.4%, 3.19%, and 3.04% of the samples exceeded the limit values of Cd, Pb, As and Cr, respectively. No limits have been set for Cu, Zn and Ni in China, and 35.0%, 13.3% and 16.7% of the samples exceeded the Cu, Zn and Ni limits for composts in Germany, respectively. Monte Carlo simulations indicated that with the continuous application of organic fertilizer, Cu, Zn, Cd, Pb and Cr would accumulate to the risk control standard for soil contamination of agricultural land (GB15618-2018) within a relatively short period. It is urgent to establish suitable limits of heavy metals in organic fertilizer in China to control the risk of heavy metal pollution in agricultural land. Keywords: heavy metal, organic fertilizer, risk assessment, maturity indices DOI: 10.25165/j.ijabe.20181106.4671 Citation: Zhang X, Meng H B, Shen Y J, Li J, Wang J R, Zhou H B, et al. Survey on heavy metal concentrations and maturity indices of organic fertilizer in China. Int J Agric & Biol Eng, 2018; 11(6): 172–179.